2022
DOI: 10.1038/s41467-022-32921-w
|View full text |Cite
|
Sign up to set email alerts
|

Expanding the terpene biosynthetic code with non-canonical 16 carbon atom building blocks

Abstract: Humankind relies on specialized metabolites for medicines, flavors, fragrances, and numerous other valuable biomaterials. However, the chemical space occupied by specialized metabolites, and, thus, their application potential, is limited because their biosynthesis is based on only a handful of building blocks. Engineering organisms to synthesize alternative building blocks will bypass this limitation and enable the sustainable production of molecules with non-canonical chemical structures, expanding the possib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
23
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(24 citation statements)
references
References 57 publications
1
23
0
Order By: Relevance
“…Davies et al have reported optimized expression ratio between P450s G8H and its redox partner increases the production of the insect-repellent nepetalactone 86 . It has been shown that combined synthetic biology and protein engineering allows to identify a suitable cytochrome P450 to decorate the terpene scaffolds leading to produce 28 different noncanonical terpenes 87 . Concerning several ambiguities about obtaining catalytically active heterologous enzymes (naturally occurring in plants), yeast must be engineered with multiple gene isoforms to identify the optimal enzyme variant.…”
Section: Combinatorial Optimization Librarymentioning
confidence: 99%
“…Davies et al have reported optimized expression ratio between P450s G8H and its redox partner increases the production of the insect-repellent nepetalactone 86 . It has been shown that combined synthetic biology and protein engineering allows to identify a suitable cytochrome P450 to decorate the terpene scaffolds leading to produce 28 different noncanonical terpenes 87 . Concerning several ambiguities about obtaining catalytically active heterologous enzymes (naturally occurring in plants), yeast must be engineered with multiple gene isoforms to identify the optimal enzyme variant.…”
Section: Combinatorial Optimization Librarymentioning
confidence: 99%
“…S -Adenosylmethionine (SAM)-dependent methyltransferases play an important role in diversifying natural products and changing their biological activities. , Majority of methyltransferases undergo the S N 2-type nucleophilic substitution reaction in which the methyl group is donated to a variety of electron-rich chemical groups. This reaction mechanism has been harnessed to introduce structural diversity to natural products and expand the biosynthetic capacity.…”
Section: Introductionmentioning
confidence: 99%
“…This reaction mechanism has been harnessed to introduce structural diversity to natural products and expand the biosynthetic capacity. Many methyltransferases have been engineered to accept non-native substrates, produce alternative products, , and introduce a different donor group. , Recently, we have tailored a promiscuous methyltransferase (pMT) to convert psi-ionone to irone, a premium flavor and fragrance molecule . By mutating the active site residues, we generated the pMT7 mutant, containing Y200F, S182E, L273V, L180A, A202L, and Y65F mutations, which was the most specific toward cis -α-irone production from psi-ionone.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Accessible and widespread chemical raw materials, such as terpenes and terpenoids, belong to an important group of biologically active natural compounds and may serve as aforementioned secondary building blocks. [36][37][38][39][40][41][42][43][44] Due to the absence of conventional donor groups, terpenes and terpenoids generally lack coordination ability. 45 Combining them with azaheterocyclic moieties of synthetic origin such as daf and dafo opens up prospects for the design of hybrid chiral ligands featuring both suitable donor groups for binding metal ions and functional groups of natural origin.…”
Section: Introductionmentioning
confidence: 99%